2015
DOI: 10.1111/andr.12135
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of male secondary hypogonadism in moderate to severe obesity and its relationship with insulin resistance and excess body weight

Abstract: SUMMARYTo study the prevalence of male obesity-secondary hypogonadism (MOSH) in patients with moderate to severe obesity, we performed a prospective prevalence study including 100 male patients with moderate to severe obesity at a university tertiary hospital. Total testosterone (TT) and sex hormone-binding globulin (SHBG) concentrations among others were assayed in all patients. Serumfree testosterone (FT) concentration was calculated from TT and SHBG levels. Semen analysis was conducted in 31 patients. We fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
75
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(79 citation statements)
references
References 37 publications
4
75
0
Order By: Relevance
“…In another study, in 149 men aged 18 to 66 years with a mean BMI of 42.7 kg/m 2 Hofstra et al not only reported that BMI was inversely correlated with free testosterone but also that 35.6% of men with obesity exhibited free testosterone levels in the hypogonadism range. Calderón et al reported that among 100 men with a mean age of 40.5 years and BMI ≥ 35 kg/m 2 , 45% could be classified as hypogonadal based on low free testosterone levels. In addition, the authors found that low free testosterone levels were associated with increased insulin resistance and low ejaculate volume.…”
Section: Obesity Prompts Hpt Axis Dysfunctionsupporting
confidence: 58%
“…In another study, in 149 men aged 18 to 66 years with a mean BMI of 42.7 kg/m 2 Hofstra et al not only reported that BMI was inversely correlated with free testosterone but also that 35.6% of men with obesity exhibited free testosterone levels in the hypogonadism range. Calderón et al reported that among 100 men with a mean age of 40.5 years and BMI ≥ 35 kg/m 2 , 45% could be classified as hypogonadal based on low free testosterone levels. In addition, the authors found that low free testosterone levels were associated with increased insulin resistance and low ejaculate volume.…”
Section: Obesity Prompts Hpt Axis Dysfunctionsupporting
confidence: 58%
“…In this clinical study, hypoandrogenemia was associated with the degree of obesity and with impaired erectile function, although the latter was assessed by anamnesis, not with a validated test such as the IIEF‐5 questionnaire. Also, Calderón et al , in a small study involving 100 male patients with moderate to severe obesity, found a prevalence of hypogonadism of 44% when considering decreased TT concentrations and of 34% according to reduced FT concentrations. On the other hand, when men with severe obesity are evaluated, the prevalence of hypoandrogenemia is even higher.…”
Section: Discussionmentioning
confidence: 99%
“…For example, hypogonadism secondary to obesity is common, with bariatric surgery correcting a significant percentage of infertility (Calderon et al, 2015, Milone et al, 2015). Similarly, patients with eating disorders have increased spontaneous abortions and miscarriages (Linna et al, 2013).…”
Section: Discussionmentioning
confidence: 99%